2012
DOI: 10.1002/jsfa.5833
|View full text |Cite
|
Sign up to set email alerts
|

Lipid stability during the frozen storage of fillets from silver catfish exposed in vivo to the essential oil of Lippia alba (Mill.) NE Brown

Abstract: The essential oil of L. alba used as sedative in the water to transport silver catfish can delay lipid oxidation of fillets during frozen storage. Thus L. alba may be a promising source of natural active compounds for use in aquaculture and the food industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 35 publications
6
16
0
8
Order By: Relevance
“…The formation of peroxides and TBARS was lower in the frozen fillets of silver catfish transported with either 30 or 40 µL L -1 of EO (Veeck et al, 2013). In the present study, lower levels of ascorbic acid were also observed in the liver of silver catfish transported in water containing the EO from L. alba.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The formation of peroxides and TBARS was lower in the frozen fillets of silver catfish transported with either 30 or 40 µL L -1 of EO (Veeck et al, 2013). In the present study, lower levels of ascorbic acid were also observed in the liver of silver catfish transported in water containing the EO from L. alba.…”
Section: Discussionsupporting
confidence: 57%
“…N.E. Brown (Verbenaceae) is a novel anesthetic whose action has been established for the silver catfish Rhamdia quelen (Cunha et al, 2010;Heldwein et al, 2012), and the slender seahorse Hippocampus reidi (Cunha et al, 2011).When this oil was added to the transport water, the redox state (Azambuja et al, 2011) and ionoregulation (Becker et al, 2012) were improved, and lipid oxidation was delayed in the fillets of silver catfish (Veeck et al, 2013). However, an increased ventilation rate was observed during the 30 min of transport (Becker et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, α-citral is the main component, followed by β-citral and limonene (PARODI et al, 2012), all of which are considered to be safe food additives for human consumption by regulatory agencies in the U.S. Treatment with EOAT during transport did not modify the proximate composition of the fish fillets, which presented mean composition (3.0±0.6% fat, 13.4±1.0% protein, 1.1±0.0% ash and 80.3±1.4% moisture), for all of the treatments (n=9), similar to those reported by VEECK et al (2013) for the species.…”
Section: Resultssupporting
confidence: 82%
“…These results indicated that exposure to 40µL L -1 EOAT during transport led to an antioxidant effect on the frozen fillets, by delaying the degradation of primary lipid oxidation products (CD) into secondary products (TBARS). Similar results were found in fillets sprinkled with Lippia alba extracts and in fillets from fish exposed in vivo to the essential oil of L. alba, which showed delayed degradation of hydroperoxides into secondary oxidation products (TBARS), indicating an antioxidant activity (VEECK et al, 2013;. In fact, some antioxidants (e.g., tocopherols) can increase primary lipid oxidation products by donating hydrogen to a peroxyl radical to form a lipid hydroperoxide while simultaneously decreasing the formation of low molecular weight volatile secondary oxidation products (DECKER et al, 2005).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation